Integrated Farming Systems for Food and Nutritional Security in North Western Himalayas - Dadhwal, K. S.; Tomar, J. M. S.; Muruganandam, M.; Kaushal, R.; Chaturvedi, O. P. (Indian Forester, 2012)
North-western Himalayan region of India is blessed with vast natural resources, yet confronted with poor quality of life. Agriculture in the region is very subsistence in nature mainly to meet the livelihood and food requirements of the households. The agriculture productivity in the region is very low due to a variety of reasons including rainfed farming and low input usage. In the region, farming systems on integrated watershed management basis can be promoted for diversification, improving livelihood, soil quality and food security. Besides, it can also be helpful in soil amelioration, stabilization of degraded lands and mitigation of the impacts of climate.